2019
DOI: 10.1111/eje.12431
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a diagnostic workshop on undergraduate teaching‐learning process for the diagnosis and management of tooth restorations—A randomised controlled study

Abstract: Objective:The aim of this study was to investigate the impact of a diagnostic workshop on undergraduate teaching-learning process for the diagnosis and management of tooth restorations. Methods:The first stage of the study was a randomised controlled study with two parallel groups: lecture (L) and lecture coupled with a diagnostic workshop (LW). A pool of cases of tooth restorations including secondary caries and marginal defects was used for training. Theoretical knowledge, perception about the activity and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 45 publications
(74 reference statements)
0
0
0
Order By: Relevance
“…For both groups, there was a significant increase in the percentage of correct answers (81.60%-test group and 79.92-control group). The results showed that the class was effective in improving short-term theoretical knowledge in agreement with the findings of Signori et al 13 However, long-term knowledge retention should be evaluated in the future, as the time frame for assessing knowledge retention can span from 2 weeks to 1 year. [31][32][33] The comparison of correct answers means and the multi-level regression showed an improvement in the students' skills to diagnose ETW lesions and their different levels after the practical activity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…For both groups, there was a significant increase in the percentage of correct answers (81.60%-test group and 79.92-control group). The results showed that the class was effective in improving short-term theoretical knowledge in agreement with the findings of Signori et al 13 However, long-term knowledge retention should be evaluated in the future, as the time frame for assessing knowledge retention can span from 2 weeks to 1 year. [31][32][33] The comparison of correct answers means and the multi-level regression showed an improvement in the students' skills to diagnose ETW lesions and their different levels after the practical activity.…”
Section: Discussionsupporting
confidence: 88%
“…al, is that most of students in the classroom were invited to participate with a response rate of 96%, reducing the common selection bias in this type of pedagogical study. 12,13,39 Another limitation was the use of images instead of only extracted tooth. It was very difficult to find teeth with different BEWE scores in a sufficient number for the training and for the practical knowledge assessment.…”
Section: Ta B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…En este sentido, la instrucción de los estudiantes para detectar correctamente las lesiones de caries no se puede descuidar y requiere así la aplicación de metodologías pedagógicas apropiadas. [11][12][13][14][15] En Brasil, la Facultad de Odontología de la Universidad de São Paulo (FOUSP) implementó en 2009, junto a la disciplina de Odontopediatría, una estrategia pedagógica innovadora dirigida a enseñar el diagnóstico de caries a estudiantes de pregrado 8, 9 . Se trata de una actividad complementar a la clase teórica (estrategia más usada) y consiste en un entrenamiento teórico-práctico, realizado en laboratorio con la mediación de tutores, donde existe la evaluación de dientes extraídos con caries y una discusión de casos clínicos.…”
Section: Introductionunclassified
“…Se trata de una actividad complementar a la clase teórica (estrategia más usada) y consiste en un entrenamiento teórico-práctico, realizado en laboratorio con la mediación de tutores, donde existe la evaluación de dientes extraídos con caries y una discusión de casos clínicos. La efectividad de esta metodología ya fue comprobada 8,10 , y otras universidades nacionales e internacionales comenzaron también a aplicarla, inclusive para la enseñanza de otros asuntos 11 . Los resultados observados de manera inmediata son bastante positivos, pero, no podemos pensar solo en la efectividad a corto plazo, ya que este tipo de esfuerzos realizados para mejorar los métodos de enseñanza en la odontología en general, exhortan una evaluación continua de las estrategias educativas aplicadas y de su impacto en el desarrollo de habilidades de los educandos, tanto como en la retención de esos conocimientos adquiridos.…”
Section: Introductionunclassified